Stability of Risk Preferences During COVID-19: Evidence From Four Measurements - Zhang, Peilu; Palma, Marco A. (Frontiers in Psychology, 2022)
This paper studies the stability of risk-preference during the COVID-19 pandemic. The results differ between risk-preference measurements, and also men and women. We use March 13th 2020, when President Trump declared a national state of emergency as a time anchor to define the pre-pandemic and on-pandemic periods. The pre-pandemic experiment was conducted February 21, 2020. There are three on-pandemic rounds conducted 10 days, 15 days, and 20 days after the Covid-19 emergency declaration. We include four different risk-preference measures. Men are more sensitive to the pandemic and become more risk-averse based on the Balloon Analogue Risk Task. Women become more risk-averse in the Social and Experience Seeking domains based on the results from the Domain-Specific Risk-Taking and Sensation Seeking Scales. Both men's and women's risk-preference are stable during COVID-19 based on a Gamble Choice task. The results match our hypotheses which based on the discussion about whether the psychological construct of risk-preference is general or domain-specific. The differential outcomes between incentivized behavioral and self-reported propensity measures of risk-preference in our experiment show the caveats for studies using a single measure to test risk-preference changes during COVID-19.